Comprehensive glycoscience - Barchi, Joseph J. (Elsevier, 2021)
Comprehensive Glycoscience, Second Edition assembles the top minds in this area who provide an update on the renowned 2007 first edition, including new discoveries and latest advances in glycoscience-related research areas such as glycan microarrays, carbohydrate materials, glycoengineering and microbiome research. The result is an up-to-date work which will impress readers with the many new advances that are outlined and taught in this second edition. Most areas of the original edition have been majorly updated, some overlapping topics have been consolidated, and several topics have been rearranged into more appropriate sections.